Being safe, feeling safe, and stigmatizing attitude among primary health care staff in providing multidrug-resistant tuberculosis care in Bantul District, Yogyakarta Province, Indonesia - Ari Probandari; Hary Sanjoto; Melani Ratih Mahanani; Luthfi Azizatunnisa; Sampir Widayati (BMC, 2019)
Abstract Introduction Patient-centered care approach in multidrug-resistant tuberculosis care requires health worker safety that covers both being safe and feeling safe to conduct the services. Stigma has been argued as a barrier to patient-centered care. However, there has been relatively little research addressing the issues of safety and stigma among health staff. This paper explored the issue of being safe, feeling safe, and stigmatizing attitude among health staff working with multidrug-resistant tuberculosis cases in primary health care facilities in Indonesia. Methods Using a mixed methods research design, data was collected with structured questionnaires among 123 staff, observations of infection control in 17 primary health care facilities, and in-depth interviews among 22 staff. Results The findings showed suboptimal infection control infrastructures for the primary health care facilities. The knowledge and motivation to follow multidrug-resistant tuberculosis care protocols are suboptimal. Feeling unsafe is related to stigmatizing attitude in providing multidrug-resistant tuberculosis care. Conclusion Being safe, feeling unsafe, and stigmatizing attitude are challenges in providing patient-centered multidrug-resistant tuberculosis care in primary health care facilities in Indonesia. Serious efforts are needed on all levels to ensure safety and prevent irrational stigma.